Effects of Intermittent Hypoxia in Training Regimes and in Obstructive Sleep Apnea on Aging Biomarkers and Age-Related Diseases: A Systematic Review - Belay Tessema; Belay Tessema; Belay Tessema; Ulrich Sack; Brigitte König; Zoya Serebrovska; Egor Egorov (Frontiers in Aging Neuroscience, 2022)
Several studies have assessed the effects of intermittent hypoxia-normoxia training (IHNT), intermittent hypoxia-hyperoxia training (IHHT), and obstructive sleep apnea (OSA) on aging and age-related diseases in humans; however, the results remain contradictory. Therefore, this review aims to systematically summarize the available studies on the effects of IHNT, IHHT, and OSA on aging and age-related diseases. Relevant studies were searched from PubMed, Google Scholar, Cochrane Library databases, and through manual searching from reference lists of eligible studies. A total of 38 eligible studies were included in this systematic review. IHHT and IHNT provide positive effects on several age-related parameters including quality of life, cognitive and physical functions, plasma level of glucose and cholesterol/LDL, systolic blood pressure, red blood cells, and inflammation. Moreover, moderate intermittent hypoxia induces telomerase reverse transcriptase (TERT) activity and telomere stabilization, delays induction of senescence-associated markers expression and senescence-associated β-galactosidase, upregulates pluripotent marker (Oct4), activates a metabolic shift, and raises resistance to pro-apoptotic stimuli. On the contrary, intermittent hypoxia in OSA causes hypertension, metabolic syndrome, vascular function impairment, quality of life and cognitive scores reduction, advanced brain aging, increase in insulin resistance, plasma hydrogen peroxide, GSH, IL-6, hsCRP, leptin, and leukocyte telomere shortening. Thus, it can be speculated that the main factor that determines the direction of the intermittent hypoxia action is the intensity and duration of exposure. There is no direct study to prove that IHNT/IHHT actually increases life expectancy in humans. Therefore, further study is needed to investigate the actual effect of IHNT/IHHT on aging in humans.Systematic Review Registrationwww.crd.york.ac.uk/prospero, identifier CRD42022298499.